Analysis of Symmetric and Asymmetric Effects of Exchange Rate Pass-Through in Inflation-Targeting Countries - Syamad; Handoyo, Rossanto Dwi (Jurnal Ilmu Ekonomi Terapan, 2023)
The main purpose of this study is to analyze the effects of symmetry and asymmetry of the exchange rate pass-through in Middle-Income and High-Income countries that implement inflation-targeting policies. This study uses a sample of Middle-Income Countries (South Africa, Brazil, India, Indonesia, and Mexico) and High-Income Countries (Australia, Japan, Canada, Norway, and Sweden) in the form of time-series 2000:Q1- 2021:Q4 with the method of Autoregressive Distribution Lag (ARDL) and Nonlinear Autoregressive Distributed Lag (NARDL). The results showed that five countries have a significant positive effect on the real exchange rate on inflation in the short-run in the ARDL method. In addition, in the NARDL method, five countries significantly positively affect the depreciation of the real exchange rate on inflation in the short-run. Then, only one country has a significant negative effect between the appreciation of the real exchange rate on inflation in the short-run and eight countries in the long-run. Based on the estimation results, it can be concluded that the average quantity of real exchange rate effect on inflation (exchange rate pass-through) in Middle-Income Countries is greater than in High-Income Countries. Therefore, inflation-targeting policies are more flexible to be applied in high-income countries. In addition to the exchange rate, other variables such as oil prices, money supply, and real GDP also greatly affect inflation and have different effects in each country.